New Governmental Regulatory System for Stem Cell–Based Therapies in Japan. (November 2014) - Hara, Akinori; Sato, Daisaku; Sahara, Yasuyuki
Regenerative medicine using stem cells is expected to provide tools for the replacement or repair of damaged tissues, opening up the possibility of treating many diseases that cannot otherwise be effectively treated. To promote the development of and access to regenerative medicine, it is important to take a balance of expedited provision of innovative therapies and appropriate steps to ensure safety and efficacy. While most developed countries have various regulatory frameworks for clinical trials and medical treatments involving stem cells, the Act on the Safety of Regenerative Medicine and the Revised Pharmaceutical Affairs Law have recently been simultaneously passed by the Japanese Diet. According to the former act, these medical technologies are categorized into 3 classes depending on their anticipated potential risk to human health, and the specific procedures falling into each class are determined. In addition, the act enables medical institutions to commission cell processing by business facilities outside the institution (even foreign facilities) that fulfill the requirements set out by the Ministry of Health, Labour and Welfare, with the aim to promote collaboration between academia and industry from an early stage. According to the latter law, a therapeutic product for regenerative medicine is defined as a product distinct from pharmaceuticals and medical devices, enabling regenerative medical products to be given a conditional, time-limited marketing authorization much earlier than that under the previous system. The new legal framework of regenerative medicine is expected to achieve the aim to develop and promote regenerative medicine, aiming at timely provision of safe and effective therapies and products.